Analysis of the labyrinth figure in the paratext of Patrick Modiano’s novels - Sarhan, Hassan (Dirasat: Human and Social Sciences, 2020)
This research aims to identify, under the methodological authority of the semiology of the image, the presence of the labyrinth figure in the paratext of some novels by Patrick Modiano. The choice and the examination of the links that the paratext of the novels of this author establishes with the labyrinthine figure is justified by the fact that this subject never attracted the attention in the works dedicated to the French writer, crowned by the Nobel prize in literature of 2014. As we will see in this work, the paratext of Modiano’s novelistic work relies heavily on the shape of the labyrinth or its symbols that emerge in a very obvious way in the illustrations, notes that precede the actual novelistic texts as well as in the back cover of some modern works